Antagonistic activity of strains of lactic acid bacteria isolated from Carpathian cheese - Musiy, L. Y.; Tsisaryk, O. Y.; Slyvka, I. M.; Kushnir, I. I. (Regulatory Mechanisms in Biosystems, 2020)
A promising area for improving probiotics is the search for new sources of strains and the development of complex preparations which would include different types of bacterial cultures that complement each other. Sources of selection may be traditional dairy products, in particular, cheeses made from raw milk. Wild strains can be endowed with antibacterial properties. The antagonistic action of lactic acid bacteria (LAB) has long attracted the attention of researchers and scientists. The aim of the study was to investigate the antagonistic activity against pathogenic and opportunistic microorganisms of LAB strains isolated from traditional Carpathian cheese. Three samples of cheese were selected for the research – one sample of brynza and budz (brynza before salting), made in the highlands of the Carpathians, and one sample of budz, made in the foothills. LAB were identified using classic microbiological and modern molecular genetic methods (RAPD-PCR, RFLP-PCR, 16S rRNA gene sequencing). The objects of our studies were five strains of LAB: Lactococcus lactis IMAU32258, L. garvieae JB2826472, Enterococcus durans FMA8, E. faecium L3-23, E. faecium IMAU9421. Technological parameters such as acid-forming activity of milk fermentation, resistance to high concentrations of NaCl and temperature optimums of cultivation were taken as the main criteria for assessing the suitability of LAB for inclusion in fermentation preparations. Antagonistic activity was determined by agar diffusion (agar well method) and optic density of test cultures using a Multiscan FC microplate reader (Thermo scientifiс, USA) at the wave of 620 nm. There were four reference strains of pathogenic and opportunistic microorganisms were test cultures: Listeria monocytogenes PCM 2191, Staphylococcus aureus PCM 458, Escherichia coli PCM 2208, Salmonella typhimurium PCM 2182. Strains of the test cultures were received from the collection of microorganisms of the Institute of Biology and Biotechnology the (University of Rzeszów, Poland). According to the ability of LAB strains to form lactic acid, L. lactis IMAU32258 was the best acid-forming agent with an acid-forming energy of 94 °T. E. faecium was characterized by moderate levels of active and titratable acidity. Less pronounced acid-forming ability was determined for the species E. durans and L. garvieae. Cultures of the genus E. faecium, L. garvieae and E. durans were the most resistant to high concentrations of NaCl (6.5%). Regarding temperature optimums, we found that strains of E. faecium and E. durans species grew both at temperatures of 10, 15 and 45 °C, whereas no growth of L. lactis IMAU32258 and L. garvieae JB282647 2 was observed at 45 °C. Among the studied bacteria, the strains of E. durans FMA8 and E. faecium L3-23 were characterized by the highest antagonistic activity in producing the largest zones of growth inhibition and optic density of pathogenic and opportunistic microorganisms. The strain L. garvieae JB282647 2 exhibited the lowest level of antagonistic activity against pathogenic and opportunistic microorganisms.